Tuberculosis-Associated Immune Reconstruction Inflammatory Syndrome (TB-IRIS) in HIV-Infected Patients: Report of Two Cases and the Literature Overview - Klaudija Viskovic; Josip Begovac (Case Reports in Infectious Diseases)
We describe two HIV-infected patients with tuberculosis-associated immune reconstruction inflammatory syndrome (TB-IRIS): one with “paradoxical” IRIS and the other with “unmasking” IRIS. TB-IRIS in HIV-infected subjects is an exacerbation of the symptoms, signs, or radiological manifestations of a pathogenic antigen, related to recovery of the immune system after immunosuppression. We focused on the radiological characteristics of TB-IRIS and the briefly literature review on this syndrome.